The Impact of Greenhouse Gas Emissions on GDP per Capita: A Multi-Scale Analysis Using the Wavelet Approach - Ouattara, Kifory; Gniza, Daniel Innocent (International Journal of Energy Economics and Policy, 2025)
This study investigates the dynamic relationship between greenhouse gas (GHG) emissions and GDP per capita in Côte d’Ivoire over the period 1991-2023. Using the continuous wavelet transform (CWT), we explore the time-frequency interactions between carbon dioxide (CO2) emissions and economic growth. Unlike conventional econometric models, the wavelet approach allows for the decomposition of signals into multiple time scales, thereby capturing both short-term fluctuations and long-term structural patterns. The results reveal that GDP per capita exhibits strong spectral activity at medium-term scales, corresponding to significant macroeconomic shifts. CO2 emissions also demonstrate medium- and long-term cyclical patterns, suggesting structural transformations in energy consumption and production. Wavelet coherence analysis confirms a robust, scale-dependent correlation between GDP and CO2, particularly at intermediate scales, highlighting a persistent coupling between economic growth and environmental impact. These findings underscore the importance of adopting multiscale tools to inform climate and economic policy in developing countries.